Modeling Sustainability Empowerment of Orphaned Preneur Businesses from A Financial Perspective Through Productive Waqf: Evidence Indonesia and Malaysia - Rahmat, Muhammad; Sisdianto, Ersi (Abdimas Indonesian Journal, 2025)
Orphan preneurs are part of the poor who are entitled to receive assistance from waqf funds collected by philanthropic institutions and donors. The problems found when the service was carried out were the availability of capital and knowledge related to financial management and reporting which was still very weak, with the existence of the orphan preneur program and the model for sustainable management and empowerment of orphan preneur businesses through productive waqf is expected to be one of the solutions to empower the community and reduce poverty rates, and orphan preneurs can be useful for the community and its surroundings. It is very good for the orphan preneur business sustainability program to continue so that other philanthropic institutions hope to continue providing assistance on an ongoing basis.